Conceptions de l'animal au regard de dialectique objet/sujet - Michel Vidal; Laurence Simonneaux
New conceptions of the animal are suggested in the speech of different stakeholders (professionals of animals, animal rights activists), scientists within humanities or biology. The analysis of the animal status questions the traditional humanist thought, paradigm based on evolutionary naturalism to suggest a post-humanist paradigm (de Fontenay, 1998). Our research highlights the epistemological evolution of the concept of animal under the dialectical subject/object based on a bibliographic study. It leads to jeopardize the thesis related to the human exception and to consider the status of the animal as a socio-scientific issue. Its impact in the educational field is considered.